Performance of Extracellular Vesicles From Leishmania (Leishmania) infantum for Serological Diagnosis of Human and Canine Visceral Leishmaniasis - Allecineia Bispo da Cruz; Francieli Marinho Carneiro; Noemi Nosomi Taniwaki; Gislene Mitsue Namiyama; Débora Oliveira dos Santos; Katia Gomes Castellão; Isabelle Martins Ribeiro Ferreira; Roberto Mitsuyoshi Hiramoto; Vera Lucia Pereira-Chioccola (Journal of Parasitology Research)
Visceral leishmaniasis (VL) is a zoonotic disease in which dogs are the main reservoirs. Until now, the serological tests do not present satisfactory sensitivity for diagnosis of these hosts. One of the functions of extracellular vesicles (EVs) is related to immunological host response. Here, we evaluated the ability of EVs released by Leishmania (Leishmania) infantum promastigotes (Leish-EVs) to be source of antigens for use in serological diagnosis for human visceral leishmaniasis (HumVL) and canine visceral leishmaniasis (CanVL). A total of 300 sera were tested. The 155 human sera were divided into 4 groups and 145 canine sera into 3 groups. In human sera, Leish-EVs were reactive in 73/74 sera from patients with VL (Hum-VL) with 98.64% sensitivity. The 26 sera from healthy individuals (NH) and 27 from individuals with asymptomatic toxoplasmosis (ATx) were nonreagent (100% specificity). Leish-EVs-ELISA had cross-reactivity or inconclusive results in 13.5% of sera from Chagas disease patients (CD). In canine sera, Leish-EVs were reactive in 60/63 sera from dogs with CanVL (Can-VL) with 95.24% sensitivity. Leish-EVs were nonreactive in sera from 57 dogs without Can-VL (NC) and 25 with other infections (OIs) with 100% specificity. Hum-VL produced more IgG1 against Leish-EVs than IgG2, IgG3, and IgG4. Can-VL produced more IgG2 against Leish-EVs than IgG1. In conclusion, this study provides evidence that Leish-EVs released by L. (L.) infantum when used as antigen in ELISA identified the host antibodies. The methodology was effective for serological diagnosis of VL, since results exhibited good sensitivity and specificity for human and canine sera.